El futuro de la protección social ante la COVID-19: las respuestas de los países - Charlotte Bilo; Roberta Brito; Aline Peres; Mariana Balboni (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
– The COVID-19 crisis has had a huge impact on the world of social protection. The pandemic has alerted national governments and the international community to the urgency of accelerating progress in building and expanding social protection systems and programmes to leave no one behind. From 5 to 8 October 2020, the socialprotection.org team organised a global e-conference titled 'Turning the COVID-19 crisis into an opportunity: What's next for social protection?'. To further disseminate its key discussions, the socialprotection.org platform and the International Policy Centre for Inclusive Growth (IPC-IG) have developed two special issues of Policy in Focus. This first issue focuses on experiences from countries in Asia, the Middle East and North Africa, sub-Saharan Africa, and Latin America and the Caribbean, as well as the overall lessons for the future, including shock-responsive and universal social protection.
Keywords: 330; Social protection; COVID-19